Tanggapan Anak Terhadap Cara Orang Tua Mendidik Anak Sebagai Petani Kelapa Sawit di Nagari Lunang Selatan Kecamatan Lunang Kabupaten Pesisir Selatan - Tiffani Eka Putri; Jamaris Jamaris (Universitas Negeri Padang, 2018)
This research is motivated by the many children of oil palm farmers who continue the efforts of their parents to cultivate oil palm, this is allegedly because of the way parents educate children as oil palm farmers. This study aims to describe children's responses to the way parents educate children as oil palm farmers which consists of three types of ways to educate children: (a) exemplary, (b) habituation, (c) advice, (d) attention, and (e) punishment. This research includes quantative descriptive research. The population in this study were children of oil palm farmers totaling 120 people with a sample of 60 people using cluster random sampling technique. Data collection techniques used are questionnaires or questionnaires, while data analysis uses a percentage formula. The results showed that children's responses to the way parents educate children as oil palm farmers in Nagari Lunang Selatan, Lunang Subdistrict, South Coastal District which included (a) exemplary aspects were categorized very well, (b) habituation aspects were categorized very well, (c) advice aspects categorized very well, (d) aspects of attention are categorized very well, and (e) aspects of punishment are categorized very well. Keywords: Response, How to Educate Children, Oil Palm Growers